Indecopi’s bureaucratic barriers control and economic fundamental rights guardianship - Ochoa Cardich, César (2013)
This study analyzes the guardianship role on entrepreneurial freedom fundamental rights, non- discrimination in economic and property aspects exerted by the Elimination of Bureaucratic Barriers Commission from the National Institute for the Defense of Competition and IntellectualProperty (Indecopi) developed throughout resolutions and administrative cases set up by the Defense of Competition Chamber #1. This role is particularly relevant in our legal system, due to their special functions the Elimination of Bureaucratic Barriers Commission is entitled by legal mandate to establish the non- application of rules in specific cases exercising legal control. This administrative function- initially misunderstood-has proved to be an efficient tool for the guardianship of economic rights due to our judicial system ineffectiveness in contentious administrative matters. The author considers the possibility of making a constitutional reform in order to provide specialized administrative bodies, such as INDECOPI, with the quality of “primary administrative jurisdiction” whose resolutions will only be reviewed by the State Council jurisdiction.